Induction of auxetic response in needle‐punched nonwovens: Effects of temperature, pressure, and time. Issue 7 (23rd May 2016) - Verma, Prateek; Shofner, Meisha L.; Lin, Angela; Wagner, Karla B.; Griffin, Anselm C.
Abstract : We have examined the effect of temperature, pressure, and time on the magnitude of induced auxetic response in post‐manufacture‐processed needle‐punched nonwovens. Different combinations of these processing parameters – temperatures ranging from room temperature to above the glass transition temperature ( T g ) of constituent fibers, pressure of 0.49 or 2.45 MPa, and duration of 4 or 24 h – were used to process these nonwovens. This resulted in some permanent compression (defined as "compression set") and in out‐of‐plane auxetic behavior of the fabric, both of which were found to be proportional to the severity of the processing conditions employed. Milder processing conditions were found to be insufficient in producing significant compression set and hence produced little or no auxetic response. Using micro‐CT and optical video microscopy techniques, it was found that the processing conditions caused the fiber bundles present in needle‐punched nonwovens to assume a buckled/tilted state, which opened up during mechanical extension and hence were instrumental in the observed thickness increase. Out‐of‐plane Poisson's ratio with strain for as‐received and treated nonwovens.